Stop the illusory nonsense! Teaching transformative delict - Zitzke, Emile (University of the Free State, 2014)
In this article, I provide a few thoughts on what it means to teach law, specifically ‘law of delict’, ‘critically’, as a response to conservative legal culture, which, I believe, currently prevails in South African legal education. By ‘critically’ I mean compliance with broad themes of critical legal theory, especially drawing from Critical Legal Studies (CLS) and its successive theoretical progeny (Feminist Legal Theory, Critical Race Theory and Queer Theory). I will tackle this project from the point of view that Klare’s transformative constitutionalism is mandated by the Constitution, and that this theory is a South African manifestation of critique. Therefore, relying on specific aspects of transformative constitutionalism, I will highlight how we can teach delict in a constitutionally mandated transformative context by employing critical pedagogy.
Keywords: Legal education; Transformative constitutionalism; Critical legal studies; Feminist legal theory; Critical race theory; Queer theory; Law of delict